Analysis of The Role of Safety Training in Improving the Quality of Human Resources Onboard Mv. Golden Competence - Dhany, Munawar; Fauzan Azhmy, Muhammad; Pasaribu, Fajar (Sumber Belajar Sejahtera, 2024)
Efforts to save lives at sea are crucial to minimizing the impact of maritime accidents, which are often caused by human error. Maritime safety is a top priority in the shipping industry, and safety training that complies with Basic Safety Training (BST) standards is essential for enhancing the quality of human resources on board. This study aims to explore the role of safety training in improving the quality of human resources on the MV. Golden Competence. The study employs a qualitative approach using a case study method to understand phenomena in their natural context and explore various interpretations from different perspectives. Data were collected through observation, in-depth interviews, documentation, and literature review over six months. The findings indicate that safety training significantly enhances the technical skills and knowledge of the ship's crew, improves mental preparedness for emergencies, and ensures compliance with international safety regulations. Additionally, the training reduces the risk of accidents and enhances workplace safety on the ship. The conclusion of this study emphasizes that safety training is a key element in creating a safe and productive work environment in the maritime industry. Investment in safety training not only improves the quality of human resources but also supports safe and efficient ship operations and strengthens the overall ship management system.